Ruthenium(II) Polypyridyl Complexes as FRET donors: structure- and sequence-selective DNA-binding and anticancer properties - Elgar, Christopher E.; Yusoh, Nur Aininie; Tiley, Paul R.; Kolozsvári, Natália; Bennett, Laura G.; Gamble, Amelia; Péan, Emmanuel V.; Davies, Matthew L.; Staples, Christopher J.; Ahmad, Haslina; Gill, Martin R. (American Chemical Society, 2023)
Ruthenium(II) polypyridyl complexes (RPCs) that emit from metal-to-ligand charge transfer (MLCT) states have been developed as DNA probes and are being examined as potential anticancer agents. Here, we report that MLCT-emissive RPCs that bind DNA undergo Förster resonance energy transfer (FRET) with Cy5.5-labeled DNA, forming mega-Stokes shift FRET pairs. Based on this discovery, we developed a simple and rapid FRET binding assay to examine DNA-binding interactions of RPCs with diverse photophysical properties, including non-“light switch” complexes [Ru(dppz)2(5,5′dmb)]2+ and [Ru(PIP)2(5,5′dmb)]2+ (dppz = dipyridophenazine, 5,5′dmb = 5,5′-dimethyl-2,2′-bipyridine, PIP = 2-phenyl-imidazo[4,5-f][1,10]phenanthroline). Binding affinities toward duplex, G-quadruplex, three-way junction, and mismatch DNA were determined, and derived FRET donor-acceptor proximities provide information on potential binding sites. Molecules characterized by this method demonstrate encouraging anticancer properties, including synergy with the PARP inhibitor Olaparib, and mechanistic studies indicate that [Ru(PIP)2(5,5′dmb)]2+ acts to block DNA replication fork progression.